2011
DOI: 10.1177/1753465811406771
|View full text |Cite
|
Sign up to set email alerts
|

Neomacrolides in the treatment of patients with severe asthma and/or bronchiectasis: a retrospective observational study

Abstract: The results of this retrospective study suggest that neomacrolides may be useful as an add-on therapy in patients with severe asthma and/or bronchiectasis. Older age may predict good response in patients with severe asthma, whereas older age, male gender and a higher HRCT score for bronchiectasis may predict therapeutic response in patients with bronchiectasis only. Prospective controlled trials of neomacrolides in patients with severe asthma are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…The immunomodulatory effects of macrolides are thought to result in reduction in sputum volume, inhibition of virulence factor production by bacteria, diminished neutrophil influx and downregulation of IL-8 production, inhibition of NF- κβ production, and reduction in both ICAM-1 and neutrophil elastase [5154]. These immunomodulatory effects result in a reduction in pulmonary exacerbations, improved lung function, and improved quality of life [28, 5561]. The clinical improvement of subjects may take up to three months to show an effect.…”
Section: Macrolides and Bronchiectasismentioning
confidence: 99%
“…The immunomodulatory effects of macrolides are thought to result in reduction in sputum volume, inhibition of virulence factor production by bacteria, diminished neutrophil influx and downregulation of IL-8 production, inhibition of NF- κβ production, and reduction in both ICAM-1 and neutrophil elastase [5154]. These immunomodulatory effects result in a reduction in pulmonary exacerbations, improved lung function, and improved quality of life [28, 5561]. The clinical improvement of subjects may take up to three months to show an effect.…”
Section: Macrolides and Bronchiectasismentioning
confidence: 99%
“…Maintenance treatment with macrolides such as azithromycin has been proved to be effective in chronic neutrophilic airway diseases including cystic fibrosis, bronchiectasis and diffuse panbronchiolitis 9–12. In an observational study, we have demonstrated the benefits of short-term macrolide treatment in patients with severe asthma 13. Recently, erythromycin and azithromycin—added to usual therapy—have been shown to prevent exacerbations in patients with chronic obstructive pulmonary disease (COPD), a predominantly neutrophilic airway disease 14–16…”
Section: Introductionmentioning
confidence: 99%
“…In one trial, responders were older and had a longer duration of asthma [60]. Other studies have suggested that PCR identification of Mycoplasma and Chlamydophila pneumoniae or neutrophilic inflammation best identifies the macrolide responsive phenotype [61,62].…”
Section: Microbiome-driven Th2-low Asthma Phenotypementioning
confidence: 98%